2015
DOI: 10.4103/0366-6999.151662
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass Index on the Clinical Outcomes after Percutaneous Coronary Intervention in Patients ≥75 Years Old

Abstract: Background:The impact of body mass index (BMI) on the clinical outcomes after percutaneous coronary intervention (PCI) in patients ≥75 years old remained unclear.Methods:A total of 1098 elderly patients undergoing PCI with stent implantation were recruited. Patients were divided into four groups by the value of BMI: Underweight (≤20.0 kg/m2), normal weight (20.0–24.9 kg/m2), overweight (25.0–29.9 kg/m2) and obese (≥30.0 kg/m2). Major clinical outcomes after PCI were compared between the groups. The primary end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Data from study Sandeep 2011, 22 Won 2010, 25 Hidehiro 2013, 24 Ibrahim 2012 9 , Pei 2015, 30 Yohei 2015, 29 Zhi 2012, 23 Heinz 2007 19 and, Shubair 2006 18 have been used to calculate the percentage of patients with their corresponding medications during the follow-up period and have been represented in Table 4 . Studies that have not been included in this section have been ignored because they did not report the medications being prescribed at hospital discharge or during the follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…Data from study Sandeep 2011, 22 Won 2010, 25 Hidehiro 2013, 24 Ibrahim 2012 9 , Pei 2015, 30 Yohei 2015, 29 Zhi 2012, 23 Heinz 2007 19 and, Shubair 2006 18 have been used to calculate the percentage of patients with their corresponding medications during the follow-up period and have been represented in Table 4 . Studies that have not been included in this section have been ignored because they did not report the medications being prescribed at hospital discharge or during the follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in Japan and South Korea indicated that a low BMI was associated with increased risks of major cardiovascular events and death among patients undergoing PCI . However, it was perplexing that studies performed in China so far consistently showed an absence of this phenomenon . Two of these studies, analyzing the same cohort of 7895 patients undergoing PCI between January 2004 and December 2006 in a Chinese center, failed to identify any association between BMI and mortality after PCI.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] However, it was perplexing that studies performed in China so far consistently showed an absence of this phenomenon. [19][20][21] Two of these studies, analyzing the same cohort of 7895 patients undergoing…”
Section: T a B L E 1 (Continued)mentioning
confidence: 99%
See 2 more Smart Citations